2020
DOI: 10.3389/fnins.2020.00778
|View full text |Cite
|
Sign up to set email alerts
|

The Redox Biology of Excitotoxic Processes: The NMDA Receptor, TOPA Quinone, and the Oxidative Liberation of Intracellular Zinc

Abstract: This special issue of Frontiers in Neuroscience-Neurodegeneration celebrates the 50th anniversary of John Olney's seminal work introducing the concept of excitotoxicity as a mechanism for neuronal cell death. Since that time, fundamental research on the pathophysiological activation of glutamate receptors has played a central role in our understanding of excitotoxic cellular signaling pathways, leading to the discovery of many potential therapeutic targets in the treatment of acute or chronic/progressive neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 160 publications
(229 reference statements)
0
11
0
Order By: Relevance
“…MT may play an important role in determining neuronal fate by regulating the localization and concentration of intracellular free zinc [ 103 , 104 ]. Recent studies have shown that oxidative and nitrosative stress during ischemic injury induced zinc accumulation and the activation of the signaling system associated with cell death processes.…”
Section: Friendmentioning
confidence: 99%
“…MT may play an important role in determining neuronal fate by regulating the localization and concentration of intracellular free zinc [ 103 , 104 ]. Recent studies have shown that oxidative and nitrosative stress during ischemic injury induced zinc accumulation and the activation of the signaling system associated with cell death processes.…”
Section: Friendmentioning
confidence: 99%
“…To gain some further insight, we focused on two distinguishing features of the NMDARs and the nNOS (+) subpopulation. NMDARs are modulated by oxidizing and reducing agents, which decrease or potentiate the amplitude of receptor response to agonists, respectively (Aizenman et al, 1989(Aizenman et al, , 1990(Aizenman et al, , 2020. On the other hand, nNOS (+) neurons fail to generate ROS of mitochondrial origin following the activation of NMDARs (Canzoniero et al, 2013;Granzotto and Sensi, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…NMDAR ionic conductance can be modulated by oxidizing/reducing agents (Aizenman et al, 1989(Aizenman et al, , 1990(Aizenman et al, , 2020. We evaluated, in nNOS (+) and nNOS (-) neurons, NMDAR activity before and after pharmacological manipulation set to alter the redox status of the receptor (Fig.…”
Section: Compared To Nnos (-) Nnos (+) Neurons Show Reduced Nmdar-driven [Ca 2+ ] I Rises Following Receptor Reductionmentioning
confidence: 99%
“…Finally, Zn 2+ mobilization, by contributing to the activation of the CamKII/p38/syntaxin/calcineurin axis, promotes outward potassium (K + ) currents, a critical step in the production of neuronal apoptosis (Yu et al, 1997;McCord and Aizenman, 2013;Shah and Aizenman, 2014;Aizenman et al, 2020).…”
Section: Zinc As Neurotoxinmentioning
confidence: 99%